Contribution of molecular analyses in diagnosing Marfan syndrome and type I fibrillinopathies: an international study of 1009 probands. Issue 6 (29th February 2008) - Faivre, L; Collod-Beroud, G; Child, A; Callewaert, B; Loeys, B L; Binquet, C; Gautier, E; Arbustini, E; Mayer, K; Arslan-Kirchner, M; Stheneur, C; Kiotsekoglou, A; et al.
Abstract : Background: The diagnosis of Marfan syndrome (MFS) is usually initially based on clinical criteria according to the number of major and minor systems affected following international nosology. The number of FBN1 mutation carriers, at risk of aortic complications who would not be properly diagnosed based only on clinical grounds, is of growing importance owing to the increased availability of molecular screening. The aim of the study was to identify patients who should be considered for FBN1 mutation screening. Methods: Our international series included 1009 probands with a known FBN1 mutation. Patients were classified as either fulfilling or not fulfilling "clinical" criteria. In patients with unfulfilled "clinical" criteria, we evaluated the percentage of additional patients who became positive for international criteria when the FBN1 mutation was considered. The aortic risk was evaluated and compared in patients fulfilling or not fulfilling the "clinical" international criteria. Results: Diagnosis of MFS was possible on clinical grounds in 79% of the adults, whereas 90% fulfilled the international criteria when including the FBN1 mutation. Corresponding figures for children were 56% and 85%, respectively. Aortic dilatation occurred later in adults with unfulfilled "clinical criteria" when compared to the Marfan syndrome group (44% vs 73% at 40 years, p<0.001), but the lifelong risk for ascending aortic dissection or surgery was not significantly different in both groups. Conclusions: Because of its implications for aortic follow-up, FBN1 molecular analysis is recommended in newly suspected MFS when two systems are involved with at least one major system affected. This is of utmost importance in patients without aortic dilatation and in children.